'Down with Big Brother!' The End of 'Corporate Culturalism'?. (13th June 2012) - Fleming, Peter
abstract Hugh Willmott's classic 1993 JMS article, 'Strength is Ignorance; Freedom is Slavery', has greatly influenced how we understand culture management. It draws parallel's with George Orwell's Nineteen Eighty‐Four to reveal the totalitarian aspirations of 'corporate culturalism'. While it is sometimes said that employee resistance is missing in Willmott's account, I argue that it is implicitly pervasive, prefiguring subsequent investigations of 'micro‐emancipation' in management studies. The recent waning of scholarly interest in this type of resistance, however, also points to the contemporary relevance of Willmott's analysis. Emergent forms of corporate regulation utilize 'biopower' rather than just cultural conformity, rendering micro‐emancipation inadequate, but inspiring other types of dissent.